2016
DOI: 10.2337/dc15-2450
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Use of Lipid-Lowering Therapy and Cardiovascular Diseases and Death in Individuals With Type 1 Diabetes

Abstract: OBJECTIVETo evaluate the effect of lipid-lowering therapy (LLT) in primary prevention on cardiovascular disease (CVD) and death in type 1 diabetes. RESEARCH DESIGN AND METHODSWe used the Swedish National Diabetes Register (NDR) to perform a propensity score-based study. Propensity scores for treatment with LLT were calculated from 32 baseline clinical and socioeconomic variables. The propensity score was used to estimate the effect of LLT in the overall cohort (by stratification). We estimated risk of acute my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 23 publications
2
34
0
1
Order By: Relevance
“…The Swedish National Diabetes Registry (NDR), initiated in 1996, is a quality assurance tool with nationwide coverage, with informed consent from all participants. The registry includes data on risk factors and medication provided by trained health care professionals (9,10) and continuous work to improve the validity of the data (11). Through the personal identity number assigned to all Swedish residents (12), we linked the following Swedish national registers: the NDR; Inpatient Registry (IPR), which is part of the National Patient Register (13); the Cause of Death Registry; and the Longitudinal Database for Health Insurance and Labor Market.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The Swedish National Diabetes Registry (NDR), initiated in 1996, is a quality assurance tool with nationwide coverage, with informed consent from all participants. The registry includes data on risk factors and medication provided by trained health care professionals (9,10) and continuous work to improve the validity of the data (11). Through the personal identity number assigned to all Swedish residents (12), we linked the following Swedish national registers: the NDR; Inpatient Registry (IPR), which is part of the National Patient Register (13); the Cause of Death Registry; and the Longitudinal Database for Health Insurance and Labor Market.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The underlying mechanisms are only partly understood and even when traditional risk factors for CVD have been addressed, patients with diabetes bear significant residual risk for CVD [3]. …”
Section: Introductionmentioning
confidence: 99%
“…4 Landmark studies such as the Diabetes Control and Complications Trial, United Kingdom Prospective Diabetes Study, Collaborative Atorvastatin Diabetes Study, and several others have shown the importance of glucose-lowering therapy, statin use, blood-pressure control, and multifactorial intervention in reducing the risk of cardiovascular outcomes among patients with diabetes. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] These trial results and the clinical application of their findings, along with lifestyle interventions (including smoking cessation), are likely to have improved outcomes in patients with diabetes during the past two decades. We set out to investigate the long-term trends (1998 through 2014) in all-cause mortality and the incidence of major diabetes-related cardiovascular complications, as compared with contemporary trends in the general population.…”
mentioning
confidence: 99%